The influence of vestibular load on the heart vessel system of high qualification fencer - Pastuhova, V. A.; Andreyuk, N. L. (Journal of Education, Health and Sport, 2018)
Introduction. The article analyzes the scientific data about cardiovascular, motor and sensory reactions of athletes to vestibular irritation. The results of experimental studies which are aimed at determining influence of vestibular loading on cardiovascular indices system of fencers of high qualification of all ages. Purpose. The aim of this reserch is to investigate the effect of vestibular loading on the cardiovascular system of high qualification fencers. Methods. The research was conducted on the basis of the National University of Physical education and sports of Ukraine. The study involved 30 fencers of high qualification, having a sports rank of the master of sports (MS) and who are members of the national team of Ukraine. Experimental data were analyzed with methods of mathematical statistics. The reliability of the difference in mean values were determined according to T-criterion of Student. To assess the impact of Vestibular load, the reaction of the cardiovascular system for changes in blood pressure, calculated the magnitude of pulse pressure, endurance ratio was studied. Results. Studies have shown that the mean values of change AT and HR in response to a vestibular test in different age groups have a certain orientation. The least increase in heart rate turned out to be 23-year-old athletes. Prevailing focus on reducing the response to the rotational load in this group, there are changes in systolic pressure. In the group of 16-year-old athletes SAT has increased. And, a significant decrease in diastolic pressure was found in 16-years athletes, and athletes in age of 23 GAO have increased. Information provided will allow to improve the efficiency of medical and biological provision in sports training of fencers in different age groups. It should also be carry out further research to find correlations between the indicators of the vestibular stability of fencers and their sporting result. Originality. For the first time we have studied the effect of vestibular loading on the cardiovascular system of high qualification fencers. Conclusion. Under the influence of fencing exercises, as the athletes develop their qualifications, the direction of the cardiovascular system’s response to vestibular irritation is changing, and its severity is largely determined by the laws of age’s development of the subjects. These studies lead to the conclusion that it is important for fencers to train vestibular apparatus to improve the technique of exercising. It should also be noted that a large number of athletes showed high values of changes in the cardiovascular system.